MAKING A PROMOTIONAL VIDEO OF GEOSITE GUA KELELAWAR PADAYO INDARUNG - Saptopramono, Hendro; Handayani, Witri; Wahyuni, Nini; Yuilsa, Fharin Mutia (Bajang Institute, 2024)
This study explores the development of a promotional video for Geosite Gua Kelelawar Padayo Indarung, utilizing the Research and Development (R&D) methodology based on the Plomp model. The primary objective is to create an engaging audiovisual tool that highlights the unique features of the geosite and enhances visitor awareness. The research follows three key phases of an R&D method: the preliminary phase, which involves need analysis and planning; the prototyping phase, encompassing production and post-production activities; and the assessment phase, where experts in language and multimedia validate the video. Findings indicate that the promotional video effectively communicates the geosite’s attractions, utilizing descriptive narration and high-quality visuals. Expert feedback suggests areas for improvement, including cave characteristic, several activities done in the spot and clearer navigation information. The study concludes that a well-structured promotional video can significantly enhance public interest and engagement with Gua Kelelawar, serving as a model for similar projects in tourism promotion.